Volume cycles in the stock market : market timing through equivolume charting - Arms, Richard W. (Homewood, Ill. : Dow Jones-Irwin, 1983)
In this book, the author shows how to combine his concepts into a market trading technique that is useful for day-to-day and long range forecasting
Includes index.
osc 13/11/17
Loans
Keywords: Stocks